2022
DOI: 10.1007/s00281-022-00950-8
|View full text |Cite
|
Sign up to set email alerts
|

How genetic risk contributes to autoimmune liver disease

Abstract: Genome-wide association studies (GWAS) for autoimmune hepatitis (AIH) and GWAS/genome-wide meta-analyses (GWMA) for primary biliary cholangitis (PBC) and primary sclerosing cholangitis (PSC) have been successful over the past decade, identifying about 100 susceptibility loci in the human genome, with strong associations with the HLA locus and many susceptibility variants outside the HLA locus with relatively low risk. However, identifying causative variants and genes and determining their effects on liver cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 88 publications
1
20
0
Order By: Relevance
“…Although HLA alleles are considered to confer the risk for various autoimmune diseases, the precise mechanism remains unclear. Some studies have demonstrated that autoantigens encoded by HLA genes are expressed on the cell surface and presented to immune cells, which activates the downstream immune process (26). Thus, Chinese AIH patients with DRB1*04:05 have typical clinical traits, probably because of the proteins presented by HLA-DRB1*04:05.…”
Section: Discussionmentioning
confidence: 99%
“…Although HLA alleles are considered to confer the risk for various autoimmune diseases, the precise mechanism remains unclear. Some studies have demonstrated that autoantigens encoded by HLA genes are expressed on the cell surface and presented to immune cells, which activates the downstream immune process (26). Thus, Chinese AIH patients with DRB1*04:05 have typical clinical traits, probably because of the proteins presented by HLA-DRB1*04:05.…”
Section: Discussionmentioning
confidence: 99%
“…For all three conditions, single-nucleotide polymorphisms (SNPs) within the human leukocyte antigen region have a significant role in shaping their genetic risk (71-73); yet, several non-HLA variants have been described for PBC (74) and PSC (73), and more recently also for AIH (75). The discussion of the large topic of missing heritability is out of the scope of this review (76); however, it is worth mentioning that large portions of the heritability of AIH, PBC, and PSC are yet to be characterized (77). Whole-exome and whole-genome sequencing have clearly revealed that the identification of rare predisposing variants with large effect size is useful to fill this gap of knowledge (78,79).…”
Section: Predicting Phenotype Based On Genotype: a Supervised Learnin...mentioning
confidence: 99%
“…Evidence in AiLD is scanty, mostly available for PSC, where autosomal-like patterns of inheritance have been identified in some families (80, 81), although it is likely that AiLDs derive in most cases from the interaction of some environmental triggers on the ground of a predisposing genetic background mostly composed of common variants. That said, the utility of PRSs, which are typically based on common variants, in AiLD is still a matter of debate (77).…”
Section: Predicting Phenotype Based On Genotype: a Supervised Learnin...mentioning
confidence: 99%
“…Autoimmune liver disease (AILD) is a rare chronic immunemediated liver injury disease, mainly comprising the following three type. 1 Primary biliary cholangitis (PBC) is a type of autoimmune liver disease characterized by autoimmune-mediated destruction of the intrahepatic bile duct epithelium and chronic biliary stasis. Its histological feature is the accumulation of lymphocytes or granulomas within the portal tracts, infiltrating and damaging the epithelial cells of the bile ducts, leading to immune inflammation.…”
Section: Introductionmentioning
confidence: 99%